Severe imported malaria in a Serbian referral center - Poluga, Jasmina; Karić, Uroš; Dakić, Zorica; Katanić, Nataša; Lavadinović, Lidija; Milošević, Branko; Nikolić, Nataša; Urošević, Aleksandar; Jegorović, Boris; Pavlović, Milorad (Vojnosanitetski pregled, 2021)
Background/Aim. The World Health Organization estimates that 3.2 billion people are at a risk of being infected with malaria. Thus, the adequate diagnostic protocols for malaria, especially those aimed at determining disease severity, are paramount both in endemic and non-endemic setting. The aim of this study was to identify the demographic, parositological, clinical and laboratory characteristics associated with severe malaria in a non-endemic settings. Methods. We analyzed 22 patients with severe malaria and compared their clinical and laboratory findings with those of the patients with non-severe malaria in a search of predictors of disease severity. All patients were treated at the Infectious and Tropical Diseases University Hospital, Clinical Centre of Serbia in Belgrade, Serbia from 2000 to 2010. Results. The average age of patients with with severe malaria was 44.86 ± 12.33 years and men predominated (95.45%). The patients with severe malaria were infected Plasmodium falciparum (P. falciparum) significantly more frequently compared with those with non-severe disease (p =0.047). Jaundice was the most commonly observed feature of severe malaria, followed by anemia and renal failure. The multifactor analysis of variance showed that thrombocytopenia (p = 0.05) and high serum tumor necrosis factor-alpha levels (p = 0.02) were significantly associated with the disease severity. Conclusion. A high index of suspicion for malaria should be maintained when evaluating febrile patients returning from the malaria endemic regions. The elevated serum tumor necrosis factor-alpha levels and thrombocytopenia are associated with severe malaria in non-endemic settings.
Keywords: malaria; tumor necrosis factor-alpha; thrombocytopenia; severity of illness index; serbia.